METTL1 mediates PKM m7G modification to regulate CD155 expression and promote immune evasion in colorectal cancer - Fang Wang; Chen Yang; Fang Zheng; Yang Yan; Guifang Li; Yanyan Feng; Hejia Xu; Zilong He; Dongyan Cai; Hairong Sun; Xiaowei Qi; Yong Mao (Journal of Translational Medicine)
Abstract Background Colorectal cancer (CRC) is characterized by poor responsiveness to immune evasion and immunotherapy. RNA 7-methylguanine (m7G) modification plays a key role in tumorigenesis. However, the mechanisms by which m7G-modified RNA metabolism affects tumor progression are not fully understood, nor is the contribution of m7G-modified RNA to the CRC immune microenvironment. Methods The expression levels of Methyltransferase-like 1 (METTL1) and m7G in human tissues were determined. In this study, the effect of METTL1 on RNA m7G levels was evaluated, the effect of METTL1 on PKM mRNA modification was confirmed, the expression level of the PKM2 protein was detected, and the mechanism involved RT‒qPCR, Western blot, RNA stability analysis and RIP analysis. Lactate and H3K9 lactylation (H3K9la) induced by METTL1/PKM2 were analyzed via the extracellular acidification rate (ECAR) and lactic acid assays. Cut&Run was used to detect METTL1/PKM2-induced CD155 (PVR) transcription. In addition, METTL1 knockout mice were studied in vivo with CD155 blockers. Results We demonstrated that m7G RNA METTL1 enhances PKM2 expression by acting on PKM mRNA, leading to tumor progression and increased glycolysis. Specifically, METTL1 mediates m7G methylation of PKM mRNA and enhances the expression of its encoded PKM2, which in turn enhances glycolysis, promotes H3K9la, and activates METTL1 transcription, creating a positive feedback loop. Moreover, increased PKM2 dimer expression and nuclear translocation activated CD155 expression and induced CRC immune evasion. Conclusions Our findings reveal a general mechanism by which METTL1/PKM2/H3K9la signaling regulates RNA metabolism and highlight METTL1 targeting as a potential strategy for CRC immunotherapy.